Trans-osseous versus Anchor Repair of Acute Patellar Tendon Ruptures. Issue 7 (30th July 2018) - O'Dowd, James A.; Lehoang, David; Butler, Rebecca K.; De Witt, David; Mirzayan, Raffy
Objectives: Patellar tendon ruptures are relatively uncommon injuries. They require prompt diagnosis and surgical repair to restore the extensor mechanism of the knee. The gold standard procedure is a suture repair of the tendon, passed through trans-osseous tunnels, and tying of the sutures on the superior pole of the patella. Suture anchors have gained popularity with a recent cadaveric study demonstrating significantly less gap formation during cyclic loading and significantly higher ultimate failure loads. We present the largest series of patellar tendon repairs and compare the clinical outcomes and complications of trans-osseous (TO) and anchor (A) repair types. Methods: All patients who underwent a primary repair of a traumatic patellar tendon rupture within 45 days of injury, between 2007 and 2016, were retrospectively reviewed. Surgeries were performed at a multi-surgeon (114 surgeons), multi-center (13 centers) community-based integrated health care system. Patients with prior knee surgery, use of graft, patellar debridement for tendonitis, inferior pole avulsion fracture, concurrent knee surgery with other procedures were excluded. Patient demographic information, repair type, complications, and time from surgery to release from medical care were recorded. Results: 361 patients (374 knees) met our inclusion criteria. 13 had bilateral repairs during our study period and an additional 8 had a contralateral repair prior to our study period, for a bilateral incidence at 5.8%. The average age was 39.8 years (9 to 86 years). There were 341 males (94.5%). The most common mechanism of injury was basketball (47%), fall (19.5%), football (5.0%), and soccer (4.8%). Average time from injury to surgery was 6.3 days (range: 1- 45 days). There were 321 TO and 53 A repairs. There was no significant difference in the mean age (P=0.27), gender (P=0.79), tourniquet time (P=0.93), or BMI (P=0.78) between the two groups. There was a significant difference in re-rupture between (24 of 321) TO (7.5%) and (0 of 53) A (0%) (P=0.034). Using logistic regression, we found that TO had 3.244 times the odds of re-operation as those with A (95% CI: 0.757, 13.895. p-value: 0.1129) but did not reach signficance. The infection rate was 7.5% for A and 1.6% for TO (P= 0.160). There was no difference in time to release from medical care, 18.4 weeks for and 17.1 weeks (P=0.92). Conclusion: Compared to Anchors, primary repair of patellar tendon ruptures with trans-osseous repair had a significantly higher re-rupture rate, but there was no difference in re-operation rate, infection, or release from medical care.